Profil Asam Amino Cacing Laut Nyale Eunice Fucata Dari Perairan Wanokaka, Kabupaten Sumba Barat - Marabi, Deksi Umbu; Ndahawali, Suryaningsih (JURNAL PENGOLAHAN PERIKANAN TROPIS, 2023)
Nusa Tenggara is a traditional ritual that is carried out once a year with the aim of catching indigenous Nyale worms in its coastal waters. Nyale sea worms are members of the Annelida phylum which have been identified around 9,000 species and mostly consist of 8,000 species of Polychaeta. Nyale worms are also known by many names, including Pyak worms, Laor worms and sea worms in general. The Kendari coastal community believes in consuming sea worms as a traditional medicine, because some of the chemical compounds present in sea worms are thought to have properties that contain high protein content with efficacious properties for treating various diseases. The amino acids of sea worms consist of 2 types of acids, namely essential amino acids and non-essential amino acids which consist of 15 subindicators of amino acids. The highest essential amino acid is found in arginine, namely, 7355.37 Â± 7.21. in fresh marine worms while in freeze dry marine worms that is 2537.55 Â± 1.46.